Korporasi sebagai Subjek dalam Tindak Pidana Paten (Reformulasi Konsep Pertanggungjawaban Pidana Berdasarkan KUHP Baru Indonesia) - Syafrinaldi, Syafrinaldi; Hardiago, David; Indaryanto, Wisnu (Jurnal Legislasi Indonesia, 2024)
This study aims to analyze theoretical issues regarding the reformulation of the concept of criminal responsibility towards corporations as subjects in criminal offenses in the field of patents by using the parameters of criminal law doctrine and the new Indonesian Criminal Code. As normative legal research, this research uses statutory, historical, and conceptual approaches. The results of the study concluded that based on construction both in terms of criminal law doctrine and the new Indonesian Criminal Code, the rules regarding corporate criminal liability mechanisms for patent crimes are not recognized in Law Number 13 of 2016 concerning Patents (Patent Law). Bearing in mind that corporate criminal liability is related to patent crimes in the provisions of Article 1 point 13 of the Patent Law, the phrase "everyone" means individuals and legal entities. With the use of this term, of course this has a juridical implication that all criminal provisions in the Patent Law can only be applied to the intended legal subject (individuals and legal entities). Therefore, with this problem, projections are needed that are aimed at reformulating the Patent Law therefore that it does not only cover corporations as subjects. Alternatively, it is also aimed at reformulating the theory used and the model for imposing sanctions that can be applied therefore that it conforms to the criminal law doctrine and the corporate concept in Indonesia's new Criminal Code.